2012
DOI: 10.1371/journal.pone.0039575
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of Results from Pair and Classical Model Formulations for Different Sexually Transmitted Infections

Abstract: The “classical model” for sexually transmitted infections treats partnerships as instantaneous events summarized by partner change rates, while individual-based and pair models explicitly account for time within partnerships and gaps between partnerships. We compared predictions from the classical and pair models over a range of partnership and gap combinations. While the former predicted similar or marginally higher prevalence at the shortest partnership lengths, the latter predicted self-sustaining transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Althaus et al [18] presented three different models with empirical data and suggested using Gini coefficient to calibrate infectious disease models. Similar comparisons are done in Ong et al [19] for general infectious disease modeling to demonstrate the difference between classical models and pair formation based individual models.…”
Section: Literature Reviewmentioning
confidence: 77%
“…Althaus et al [18] presented three different models with empirical data and suggested using Gini coefficient to calibrate infectious disease models. Similar comparisons are done in Ong et al [19] for general infectious disease modeling to demonstrate the difference between classical models and pair formation based individual models.…”
Section: Literature Reviewmentioning
confidence: 77%
“…Several studies have compared the estimated impact of interventions between pair formation models and instantaneous contact model ( Althaus et al., 2012a , Heijne et al., 2011 , Lloyd-Smith et al., 2004 , Ong et al., 2012 , Van de Velde et al., 2010 ). Lloyd-Smith et al.…”
Section: Comparisons Of Pair Formation Models With Instantaneous Contmentioning
confidence: 99%
“…In 2017 the WHO added Neisseria gonorrhoeae to its priority list of bacterial pathogens in response to 21 the global spread of antibiotic resistance [1]. The bacteria have developed resistance to every therapy 22 used against them, from penicillin through to third-generation cephalosporins [2].…”
Section: Introductionmentioning
confidence: 99%
“…Compartmental models that do not explicitly represent partnerships 58 have been shown to underestimate the importance of core groups of highly sexually active individuals 59 in sustaining STI transmission, while overestimating the contribution of long-term partnerships and 60 low-activity individuals [19]. Furthermore, several studies have shown that, in order to explain observed 61 patterns of infection, it is important to take into account not only the network structure but also the 62 duration of partnerships, and the gaps between them [20,21]. It may therefore be necessary to use a 63 dynamically evolving network to correctly simulate the spread of STI outbreaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation